A Systematic Review of Definitions for Dysphagia and Dysphonia in Patients Treated Surgically for Degenerative Cervical Myelopathy. Issue 7 (September 2022) - Tetreault, Lindsay; Lange, Stefan F.; Chotai, Silky; Lupo, Mercedes; Kryshtalskyj, Michael T.; Wilson, Jefferson R.; Martin, Allan R.; Davies, Benjamin M.; Nater, Anick; Devin, Clinton; Fehlings, Michael G.
Study Design: Systematic review. Surgical decompression for degenerative cervical myelopathy (DCM) is associated with perioperative complications, including difficulty or discomfort with swallowing (dysphagia) as well as changes in sound production (dysphonia). This systematic review aims to (1) outline how dysphagia and dysphonia are defined in the literature and (2) assess the quality of definitions using a novel 4-point rating system. Methods: An electronic database search was conducted for studies that reported on dysphagia, dysphonia or other related complications of DCM surgery. Data extracted included study design, surgical details, as well as definitions and rates of surgical complications. A 4-point rating scale was developed to assess the quality of definitions for each complication. Results: Our search yielded 2, 673 unique citations, 11 of which met eligibility criteria and were summarized in this review. Defined complications included odynophagia (n = 1), dysphagia (n = 11), dysphonia (n = 2), perioperative swelling complications (n = 2), and soft tissue swelling (n = 3). Rates of dysphagia varied substantially (0.0%-50.0%) depending on whether this complication was patient-reported (4.4%); patient-reported using a modified Swallowing Quality of Life questionnaire (43.1%) or the Bazaz criteria (8.8%-50.0%); or diagnosed using an extensive protocol consisting of clinical assessment, a bedside swallowing test, evaluation by a speech and language pathologist and a modified barium swallowing test/fiberoptic endoscopy (42.9%). The reported incidences of dysphonia also ranged significantly from 0.6% to 38.0%. Conclusion: There is substantial variability in reported rates of dysphagia and dysphonia due to differences in data collection methods, diagnostic strategies, and definitions. Consolidation of nomenclature will improve evaluation of the overall safety of surgery.